2011
DOI: 10.1016/j.anifeedsci.2011.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between methane production and milk fatty acid profiles in dairy cattle

Abstract: based on the Schwarz Bayesian Information Criterion. Dry matter intake was 17.7 ± 44 1.83 kg/day, milk production was 27.0 ± 4.64 kg/day, and methane production was 45 21.5 ± 1.69 g/kg DM. Milk C8:0, C10:0, C11:0, C14:0 iso, C15:0 iso, C16:0 and 46 C17:0 anteiso were positively related (P<0.05) to methane (g/kg DM intake), whereas 47 C17:0 iso, cis-9 C17:1, cis-9 C18:1, trans-10+11 C18:1, cis-11 C18:1, cis-12 C18:1 48 and cis-14+trans-16 C18:1 were negatively related (P<0.05) to methane. Multivariate 49 analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
134
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(164 citation statements)
references
References 19 publications
20
134
5
1
Order By: Relevance
“…While some of the Grainger data were included in the present analysis, the current dairy dataset excludes all data where the concentrate proportion of the diet was over 30% and also includes data obtained since 2007 . The dairy MY is a little below that of 23.1 g CH 4 /kg DMI reported by Dijkstra et al (2011) for dairy cows in The Netherlands and slightly higher than the 19.1 g CH 4 /kg DMI reported by Hristov et al (2013aHristov et al ( , 2013b. The analysis by Hristov et al (2013aHristov et al ( , 2013b included high-concentrate diets and this probably contributed to the slightly lower MY than in our analysis.…”
Section: Methane Yieldcontrasting
confidence: 54%
See 1 more Smart Citation
“…While some of the Grainger data were included in the present analysis, the current dairy dataset excludes all data where the concentrate proportion of the diet was over 30% and also includes data obtained since 2007 . The dairy MY is a little below that of 23.1 g CH 4 /kg DMI reported by Dijkstra et al (2011) for dairy cows in The Netherlands and slightly higher than the 19.1 g CH 4 /kg DMI reported by Hristov et al (2013aHristov et al ( , 2013b. The analysis by Hristov et al (2013aHristov et al ( , 2013b included high-concentrate diets and this probably contributed to the slightly lower MY than in our analysis.…”
Section: Methane Yieldcontrasting
confidence: 54%
“…Hristov et al (2013aHristov et al ( , 2013b) also demonstrated a simple relationship between MP and DMI in a meta-analysis of dairy data that included DMI over a range similar to that in the current analysis (MP (g/day) = 19.14 · DMI + 2.54). Similarly, Dijkstra et al (2011) reported that methane yield (MY, g CH 4 /kg DMI) for dairy cows in The Netherlands was 23.1, suggesting a linear relationship between MP and DMI, with an intercept of zero. In contrast, a curvilinear relationship between MP and DMI was developed by Blaxter and Clapperton (1965), and subsequently corrected by Wilkerson et al (1995).…”
Section: Methane and Dmimentioning
confidence: 86%
“…Furthermore, this coefficient for dairy cows is less than the 23.1 g CH 4 /kg DMI (Fig. 4) reported by Dijkstra et al (2011) for dairy cows in The Netherlands, but more than the coefficient of 19.4 for diets based on a mixture of maize silage, maize grain and soybeans, as is typically used in the USA .…”
Section: Modelling Enteric Methane Productionmentioning
confidence: 66%
“…In Europe, research has focussed on the possibility of using the concentrations of specific fatty acids in milk as predictors of methane emissions from dairy cows (Chilliard et al 2009;Dijkstra et al 2011). Furthermore, the fatty acid composition of milk fat can influence the mid-infrared spectra of milk and researchers in Belgium have related the midinfrared spectrum of milk from individual cows to their methane emissions (Dehareng et al 2012;Vanlierde et al 2013).…”
Section: Proxy Measures Of Methane Emissionsmentioning
confidence: 99%
“…Importantly, Chung et al (2011) reported that dietary inclusion of linseed as a source of polyunsaturated fatty acid (PUFA) was associated with decreased CH 4 output in dairy cows when fed barley silage-, but not when fed grass hay-based diets, suggesting an important interaction with forage type, which may make prediction equations only relevant in certain scenarios. Others have reported the associations between CH 4 and milk FA across experiments using different dietary fat sources with potential negative effects on ruminal microorganisms, such as PUFA and medium-chain fatty acid (MCFA), or across different forages (Castro-Montoya et al, 2011;Dijkstra et al, 2011;van Lingen et al, 2014). It is therefore possible that these associations between CH 4 and milk FA profile might not apply when diets do not include such dietary fat supplements.…”
Section: Introductionmentioning
confidence: 99%